A new extremely hazardous viral disease in southeast Asia which affects both swine and humans - TZIKA (Ε. Δ. ΤΖΗΚΑ) E. D.; SAOULIDIS (Κ. ΣΑΟΥΛΙΔΗΣ) K.; ALEXOPOULOS (Κ. ΑΛΕΞΟΠΟΥΛΟΣ) K.; KYRIAKIS (Σ.Κ. ΚΥΡΙΑΚΗΣ) S. C. (Journal of the Hellenic Veterinary Medical Society, 2018)
Since the end of 1998, incidents of a serious viral encephalitis have been reported in Malaysia and recently in Singapore, a 50% of which led to death. According to the updated information on this new disease, its transmission is related to swine. At first, it was believed that cause of the encephalitis was the virus of the Japanese encephalitis type B. However, after the proper laboratory examinations, it was proved that a new, unknown virus was related to the etiology of the incidents. This virus belongs to the Paramyxoviridae family and has many common characteristics with the Hendra virus, without being the actual one. The first name attributed to the virus was Hendra like virus, but recently the name Nipah virus prevails.